Exploring The Relationship Between Instagram and Self-Esteem Among University Students - Willmie Wilfred; Syahruddin Awang Ahmad (International Journal of Scientific & Technology Research, 2021)
The increased number of Instagram users demonstrated that this platform is expected to grow in the current time and has the potential to influence the young generation because they are exposed to the platform on a daily basis. Instagram exposure is frequently associated with low self-esteem among users. Therefore, the current study was designed with two main objectives 1) to investigate the relationship between Instagram and self-esteem of namely university students, and 2) to investigate the influencing factor of Instagram in affecting the level of self-esteem of university students. Low self-esteem is often associated with negative emotions such as depression, antisocial behaviour, and suicidal thoughts. As for the student, self-esteem plays an important role in academic achievement as it is stated in this study which was conducted by using quantitative approach. Findings showed that student who have low self-esteem often experiencing in poor academic performance to be compared with those who have a high level of self-esteem. According to the findings, there is no significant relationship between Instagram and the third-year communication student's self-esteem. Aside from that, the results show that the number of likes on photos and videos on Instagram is an influencing factor in determining one's level of self-esteem.